2000
DOI: 10.1161/01.hyp.36.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Aldosterone Production in Genetically Hypertensive Rats

Abstract: Abstract-Aldosterone is synthesized in extra-adrenal tissues, both blood vessels and brain. We undertook the present study to determine whether the rat heart produces aldosterone and to investigate the effects of adrenalectomy, ACE inhibition, and angiotensin II on aldosterone synthesis in the heart. To clarify the pathophysiological role of cardiac aldosterone in the hypertensive heart, we compared the synthesis of aldosterone in the hearts of stroke-prone spontaneously hypertensive rats (SHRSP) with that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 41 publications
1
96
0
3
Order By: Relevance
“…In some of our experiments, aldosterone was detectable in coronary effluent, obtained during the 30 minutes of perfusion with vehicle before the collection of the heart. Although this could reflect local synthesis of aldosterone, 12 it might also represent washout of blood-derived aldosterone that had accumulated in the heart in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of our experiments, aldosterone was detectable in coronary effluent, obtained during the 30 minutes of perfusion with vehicle before the collection of the heart. Although this could reflect local synthesis of aldosterone, 12 it might also represent washout of blood-derived aldosterone that had accumulated in the heart in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 In the heart, it has been proposed that the presence of such high levels depend on local synthesis of aldosterone, although not all of the studies agree on this issue. [11][12][13] Across the human coronary vascular bed, both release and uptake of aldosterone have been observed. 14,15 In the present study, using the isolated perfused rat Langendorff heart, we first investigated whether the new and more selective MR antagonist eplerenone exerts the same cardioprotective effects as spironolactone, to additionally unravel whether these effects are MR mediated.…”
mentioning
confidence: 99%
“…13 The synthesis of aldosterone requires the aldosterone synthetase CYP11B2. 33 Several reports have shown that there isCYP11B2 mRNA expression and activity in the heart and vessel walls; 34 however, results regarding the synthesis of aldosterone in the heart and peripheral vasculature are contradictory. 35 We tried to examine the mRNA expression levels of CYP11B2 in the heart, aorta and kidney using quantitative real-time PCR, but we could not detect the expression of CYP11B2 in any tissues (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that aldosterone synthesis in local cardiac tissues and its effects are related with the process of left ventricular remodeling (26). Aldosterone blockers have been reported to suppress cardiac hypertrophy and cardiac fibrosis (27,28). Takeda et al reported that a high-salt intake accelerates the expression of the aldosterone synthase gene, CYP11B2 mRNA, in the cardiac tissues while also increasing cardiac aldosterone synthesis locally, which may affect cardiac hypertrophy independently of the RAAS in blood (29).…”
Section: Discussionmentioning
confidence: 99%